The Structural Analysis of Kazakh Fairytales - Mingisheva, N. (Вестник Карагандинского университета, 2015)
Fairytales are important part of Kazakh mythology alongside «shezhire» which represents different Kazakh genealogies including legends about origins of tribes and lineages narrated about famous persons of different lineages. The author tries to do structural analysis of Kazakh fairytales using methodology of V.Y.Propp and C.Levi-Strauss to do comparative analysis of Kazakh and Russian fairytales. In the present time researches of the Kazakh mythology are one of the important and priority investigations in Kazakhstani human sciences. There are published «shezhire» of different Kazakh lineages, which are started to reconstruct but these researches have spontaneous and mostly have only a descriptive character. The author had done the attempt of theoretical analysis of Kazakh fairytales, which are the part of Kazakh mythology.
Қазақ ертегілерін құрылымдық тұрғыдан талдау
Структурный анализ казахских сказок
Keywords: кazakh fairytales; кazakh mythology; structuralism; morphology; comparative analysis; theoretical analysis; methodology; traditional society; social structure; lineage; genealogy